Inheritances and inequality over the life cycle: what will they mean for younger generations? - Pascale Bourquin; Robert Joyce; David Sturrock (Institute for Fiscal Studies (IFS), 2021)
Inheritances have been growing as a share of national income in the UK since the 1970s. This trend looks set to continue as generations at older ages hold more wealth than their immediate predecessors but younger generations have no higher incomes than the generations born just before them. What will this mean for inequalities in living standards and wealth? Does the growth in inheritances mean people's living standards will increasingly be determined by who their parents are? If people anticipate that they are going to inherit in future, could that influence their decisions about how much to spend and save today? New IFS research, released today and funded by the Nuffield foundation, makes projections of the inheritances to be received by the 1960s, 1970s and 1980s-born generations in the UK.
Keywords: 330; Lebensstandard; Einkommensverteilung; Vermögensverteilung; Erbe; Privater Konsum; Soziale Mobilität; Lebensverlauf; Großbritannien